The energy world is flat : opportunities from the end of peak oil - Lacalle, Daniel (John Wiley & Sons, 2015)
A stronger, more informed approach to the energy markets The Energy World Is Flat provides a forward-lookinganalysis of the energy markets and addresses the implications oftheir rapid transformation. Written by acknowledged expert DanielLacalle, who is actively engaged with energy portfolios in thefinancial space, this book is grounded in experience with the worldof high-stakes finance, and relays a realist's perspective of thecurrent and future state of the energy markets. Readers will bebrought up to date on the latest developments in the area, andlearn the strategies that allow investors to profit from thesedevelopments. An examination of the markets' history drawsparallels between past and current shifts, and a discussion oftechnological advancements helps readers understand the issuesdriving these changes. Energy has always been at the forefront of the economic agenda, being both the key to and a driver for development and growth. Itscentrality to the world of finance makes it imperative forinvestors and analysts to understand the energy markets, irrespective of where on the wide range of energy spectrumobservers they fall. The Energy World Is Flat is a guide tothe past, present, and future of these crucial markets, and thestrategies that make them profitable. These include: -Understanding the state of the energy markets, including keydevelopments and changes -Discovering the ten pillars of a successful energy investmentstrategy -Reviewing the history of the energy markets to put recentchanges into perspective -Learning which technologies are driving the changes, and how itwill affect investors The recent energy market changes were both unexpected and sofundamental in nature that they represent a true shift in theenergy macro- and microeconomic landscape. Investors and analystsseeking a stronger approach to these markets need the expertguidance provided by The Energy World Is Flat.